Profile of Major Risk Factors in Acute Coronary Syndrome (ACS) at Pusat Pelayanan Jantung Terpadu (PPJT) Dr. Soetomo Public Hospital Surabaya Between the Period of January-December 2019 - Ikhsanuddin Qothi; Muhamad Robi’ul Fuadi; Agus Subagjo (Universitas Airlangga, 2021)
Background: Coronary heart disease (CHD) is a leading cause of death worldwide. One type of CHD that most often causes clinical manifestations and death is Acute Coronary Syndrome (ACS). In 2013 the prevalence of SKA in Indonesia reached 1.5% and it is estimated that it will continue to increase every year. Objective: This study aims to determine the profile of major risk factors for ACS sufferers in the Pusat Pelayanan Jantung Terpadu (PPJT) Dr. Soetomo Public Hospital Surabaya in the period January-December 2019. Methods: This study used a retrospective descriptive method to analyze the patient's electronic medical record (e-MR). Results: Out of 623 patients diagnosed with ACS, 429 were excluded from the research. 194 patients who met the inclusion criteria were studied with the following details: 19 APTS patients, 43 N-STEMI patients, and 132 STEMI patients. It was found that 73% of ACS patients were male, with the 55-64 years’ age group dominating by 46%. Based on blood pressure and serum cholesterol examination data, it was found that 51% of patients had hypertension and 77% of patients had dyslipidemia (40% hypercholesterolemia, 42% hypertriglyceridemia, 40% low HDL-C levels, and 34% high LDL-C levels). 60% patients had type-2 diabetes mellitus and 52% of patients had a history of smoking. Conclusion: 73% of ACS patients in this study were men. Most common age groups were 55-64 years old (46%), had hypertension by 51%, had dyslipidemia by 77% (40% hypercholesterolemia, 42% hypertriglyceridemia, 40% low HDL-C levels, 34% high LDL-C), had type-2 diabetes mellitus by 60%, and had a smoking history by 52%.